2022
DOI: 10.1111/nph.18372
|View full text |Cite
|
Sign up to set email alerts
|

Histone acetyltransferase TaHAG1 interacts with TaPLATZ5 to activate TaPAD4 expression and positively contributes to powdery mildew resistance in wheat

Abstract: Plants have evolved a two-branched innate immune system to detect and cope with pathogen attack, which are initiated by cell-surface and intracellular immune receptors leading to pattern-triggered immunity (PTI) and effector-triggered immunity (ETI), respectively. A core transducer including PAD4-EDS1 node is proposed as the convergence point for a twotiered immune system in conferring pathogen immunity. However, the transcriptional regulatory mechanisms controlling expression of these key transducers remain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…A previous phylogenetic study of the 62 PLATZ genes identified in wheat ( TaPLATZ1 to TaPLATZ62 ) revealed six groups (I to VI) (25), with TraesCS6A02G156600 (TaPLATZ34 ) included in Group III (25). The two previously characterized wheat PLATZ genes belong to Group I ( TaPLATZ5, TraesCS2D02G447400 ) (26) and Group II ( TaFl3, TraesCS3A02G497900 ) (27), so no functional information is currently available for wheat genes from Group III.…”
Section: Resultsmentioning
confidence: 99%
“…A previous phylogenetic study of the 62 PLATZ genes identified in wheat ( TaPLATZ1 to TaPLATZ62 ) revealed six groups (I to VI) (25), with TraesCS6A02G156600 (TaPLATZ34 ) included in Group III (25). The two previously characterized wheat PLATZ genes belong to Group I ( TaPLATZ5, TraesCS2D02G447400 ) (26) and Group II ( TaFl3, TraesCS3A02G497900 ) (27), so no functional information is currently available for wheat genes from Group III.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, during the plant–pathogen interaction, the induction of immune‐responsive genes is usually associated with increased H3 acetylation levels (Yang et al ., 2015). A recent study demonstrated that the histone acetyltransferase TaHAG1 interacts with TaPLATZ5 to activate TaPAD4 expression by increasing the levels of H3 acetylation and positively contributes to powdery mildew resistance in wheat (Song et al ., 2022). By contrast, in the absence of a pathogen, the transcription of plant defense‐related genes, as well as NLR resistance genes, are tightly controlled through the deacetylation of H3 (Yang et al ., 2020; Wu et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these genes were involved in transport, carbohydrate metabolism, catalytic activities, transcription and replication processes (Table S1). However, some of these genes have been reported to be involved in biotic stress resistance (Figure 4c) such as MLO‐like protein 1 (Jørgensen, 1992); LHP 1 (Ramirez‐Prado et al, 2019); histone acetyl transferase (Song Song et al, 2022); replication factor C (Xia et al, 2009); FAR1 (Wang et al, 2016), DEAD box RNA helicase 50 (Jadhav et al, 2018); peptidyl‐prolyl cis‐trans isomerase (Mokryakova et al, 2014); and glycosyl hydrolase family 10 (Kim et al, 2021). MLO is a transmembrane protein and provides resistance by effective arrest of fungal pathogen at early stages of prepenetration by forming enlarged cell wall apposition at the site of fungal penetration followed by callose deposition and generation of anti‐oxidants (HĂźckelhoven et al, 2000; Piffanelli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%